Identifying priority sites for the on-farm conservation of landraces and systematic diversity monitoring through an integrated multi-level hotspot analysis: the case of potatoes in Peru - Dawson, Tamsyn; Juarez, Henry; Maxted, Nigel; de Haan, Stef (Frontiers in Conservation Science, 2023)
Effective monitoring of the in situ conservation status and change dynamics of landrace populations in their centers of origin ideally requires the identification of sites that are complementary in terms of the richness, uniqueness and coverage of genetic diversity. We applied a 4-step approach to identify sites of high potato landrace diversity which will guide the set-up of a network of complementary prospective conservation observatories in Peru, the potato center of origin. A GIS mapping approach was used to determine which combination of sites would provide the most comprehensive and complementary genepool coverage. A landrace inventory was developed from 49 sources, comprising 47,272 landrace records, 97.1% with coordinates, which was used to derive landrace, cultivated species, and cultivar group richness. Data on known indicators of agrobiodiversity, including potato wild relative concurrence, cultivated area, ecogeographic diversity, and ethnolinguistic diversity were included in the spatial overlay analysis, which was used in conjunction with expert opinion data to provide further insight to hotspot selection. Thirteen hotspots with high, unique, and complementary levels of landrace diversity were identified. We recommend that robust baselines are established, documenting current diversity in these sites using semi-standardized methods and metrics for future tracking. Our results, while being the most robust of their kind to date, were inevitably affected by data gaps, infrastructure and hotspot biases. New documentation efforts should record landrace diversity in uncovered regions, as well as explore complementary mechanisms to track the conservation status of unique endemic landraces that occur in coldspots.